دراسة حول تربية الإبل وتكاثرها في الجنوب الغربي الجزائري (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
أجريت هذه الدراسة بهدف التأكيد على ضرورة الاهتمام بالإبل وتثبيت مفاهيم واضحة لتربيتها وتناسلها، اعتماداً على المعاينة والمتابعة الميدانية لثلاثين قطيعا من الإبل بلغ تعدادها 3461 رأسا موزعة على خمس مناطق. أظهرت النتائج أن إبل هذه المناطق ترعى بثلاث طرائق مختلفة هي: الترحال الدائم والترحال المؤقت والاستقرار. وتحرس بثلاث طرائق أيضا: يحرسها إما أصحابها أو مكلف بالقطيع أو راع. وتتجمع الإبل بقطعان متوسط عددها 115.36+ 50.02 رأسا. حيث مثلت الإناث النسبة الأعلى ضمن القطعان بواقع 65.44 منها51.16% نوقا .بينما بلغت نسبة الذكور 34.56%  منها 11.13% فقط لأغراض تسفيد نوق التناسل. أما بقية الإبل فكانت إما صغيرة دون سن البلوغ الجنسي أو مخصية تستخدم للنقل والأغراض الزراعية الآخرى. كان النشاط التناسلي (تزاوج, ولادات) عند الإبل في المناطق التي شملتها الدراسة ممكنا على مدار العام  باستثناء شهر أيار وذلك اعتمادا على كمية الأمطار والأعشاب . بلغ متوسط فترة الحمل عند نوق التناسل 376.37 يوما (بين 365 و391) لتأثره بعوامل مختلفة، كموسم الولادة وجنس المولود. وكانت نسبة المواليد الإناث 50.89% والذكور 49.11%. وأظهرت نوق التناسل كفاءة تناسلية تراوحت بين 52.06% و85.47% بمتوسط قدره 72.02%  أما كفاءتها الإنتاجية  فتراوحت بين 45.20% و81.10%. وبينت الدراسة أن النوق تعاني من الأمراض التناسلية وسوء التغذية والتي تؤثر سلباً في كفاءتها التناسلية والإنتاجية. This study is the based on practical visits and follow up of 30 herds having 3461 heads of camels in 5 districts. It aimed to fix a clear evidence of their breeding and reproduction. The results showed that there were 3 different ways of management (continuous traveling, temporary traveling, and permanent stay without traveling). There were 3 ways, also, of witching and dealing with the herds (by the owners themselves, responsible of the herd, and herd man). The mean number of animals in the herds was 115.36 ± 50.20. The females were more than males, with a percentage of 65.44%. From these females there were 51.16% used for reproduction. Not more than 11.13% of the male camels were used for inseminating the reproductive females, while the rests were young and / or castrated to be used for other purposes. The reproductive activity (copulation and parturition) in camels could be seen all around the year (excepted during May) in the regions of this study depending on amounts of rain and growing of grass. The mean gestation period in the reproductive female camels was 376.37 days (between 365 and 391 days) and was affected by different factors like the season of birth and sex of the fetus. The sex-ratio of the new birth was 49.11% male and 50.89% female. The reproductive ability of the female camels was good, as it reached 72.04%, while the productive ability was 66.86%. The female camels suffer from some reproductive diseases affecting their reproductive and productive abilities.